Orthodontic scars - Vinay Reddy; Vijeev Vasudevan; Gowri Sankar; A V Arun; S Mahendra; Mohammed K Khalid (Wolters Kluwer Medknow Publications, 2012)
Orthodontic therapy apart from its benefits also has potential risks and limitations in terms of tissue damage. Fortunately, in orthodontics, risks are minimal and infrequent However, all potential risks and limitations should be considered and addressed when making the decision to undergo orthodontic treatment. Orthodontic treatment carries with it the risk of various types of soft and hard tissue damages (e.g. decalcification of enamel, lacerations, ulcerations, temporomandibular joint disorders, etc-), apart from treatment failure in itself. If correcting a malocclusion is to be of benefit, the advantages offered should outweigh any possible damage- All preventive procedures should be considered during and after orthodontic treatment to restore the normal health of soft and hard tissues. Hence, the orthodontist should be vigilant and prudent enough in assessing and monitoring every aspect of these tissues at any given stage and time in order to achieve a healthy and successful final result.